Avaliação agronômica de capim marandu [Brachiaria brizantha (Hochst ex A. RICH.) STAPF. cv. Marandu] em sistemas integrados de produção - Gomes, Fagner Junior (2015)
Understanding systems that provide shade such as silvopastoral systems has been recognized as key for developing improved management techniques of those systems. Evaluation of forage plants in pastures is a way to guarantee the understanding of the mechanisms that drive systems responses. The objective of this research was to evaluate sward structural characteristics, forage accumulation and plant-part composition of Marandu palisadegrass [Brachiaria brizantha (Hochst ex A. RICH.) STAPF. cv. Marandu] in a silvopastoral system. The experiment was carried out in Sinop, State of Mato Grosso, at Embrapa Agrosilvopastoral. The experimental design was completely randomized with two treatments (production systems): Silvopastoral (SSP) and full sun (PS) where the forage was harvested to 12 cm every 28days from November 2013 to November 2014, a period that was divided into 5 seasons: late spring, summer, autumn, winter and early spring. The total forage accumulation was similar in both systems (p = 0.1495), with 7350 kg DM ha-1 in the silvopastoral system and 9000 kg DM ha-1 for full sun. There was a season x system interaction for mass of leaf, stem and dead material in the harvested forage. The leaf mass was 42% higher in summer than the other seasons, and the autumn was 63% higher in PS when compared to SSP. Sward height, LAI and LI were influenced by season (p <0.001). At preharvest sward height was greatest in the summer (23 cm) and lowest in the winter (15.5 cm), with 18, 17 and 19 cm in early spring, late spring and autumn, respectively. For LAI and LI, the highest values were registered in the summer (3.98 and 94.8%) and lowest in the winter (1.35 and 64.5%). ANG did not differ (p = 0.87) among seasons averaging 50°. At post - xi harvest, the average values of LAI varied (p < 0.0001) between 2.1 in the summer and 0.98 in the winter. The IL was affected by season (p < 0.0001) and it was higher in the summer (75.3%) and lowest in the winter (51.2%), although the autumn value was equal to that of the summer (71.6%). ANG differred (p = 0.005) only among seasons, with average values in winter, autumn and summer of 59°, 47° and 49°, respectively. The system evaluated had been established three years prior to the beginning of the experiment, and trees were, an average, 9 m high. We conclude that Marandu palisadegrass pastures in silvopastoral systems, with 30 m between rows of 9-m-high trees have forage accumulation similar to that of pastures under full sun. Plant-part composition was different in the rainy-dry and dry-rainy transition periods. Sward structural characteristics suggest that shading may start to cause morphophological and physiological responses that may reduce forage production in upcoming years.